Spray Drying of High Sugar Content Foods: Improving of Product Yield and Powder Properties - Mehmet Koç; Figen Kaymak-Ertekin (Turkish Journal of Agriculture: Food Science and Technology)
Spray drying is the most preferred drying method to produce powdered food in the food industry and it is also widely used to convert sugar-rich liquid foods to a powder form. During and/or after spray drying process of sugar-rich products, undesirable situation was appeared such as stickiness, high moisture affinity (hygroscopicity) and low solubility due to low molecular weight monosaccharides that found naturally in the structure. The basis of these problems was formed by low glass transition temperature of sugar-rich products. This review gives information about the difficulties in drying of sugar-rich products via spray dryer, actions need to be taken against these difficulties and drying of sugar-rich honey and fruit juices with spray drying method.